A new record of Impatiens kamtilongensis Toppin (Balsaminaceae) for Vietnam flora - Chinh, Vu Tien; Thanh Huong, Nguyen Thi; Quang, Bui Hong; Suksathan, Piyakaset (Academia Journal of Biology, 2015)
Impatiens kamtilongensis Toppin (Balsaminaceae), collected from Xuan Lien district, Thanh Hoa province is reported here as a new record for the flora of Vietnam. I. kamtilongensis can be distinguished from its closest ally I. finetii by its hairy white stem, yellow flowers having 2 red blotches, bigger sepals and glabrous capsule. The specimens are deposited in the Herbarium of the Institute of Ecology and Biological Resources (HN) Ha Noi, Vietnam. Morphological redescription and illustrations are provided along with notes on distribution, ecology, phenology and conservation of the species.